Assessment of Fruit Flies Infestation on Gauva in Terai Region of West Bengal - Roy, G.; Laskar, N.; Sarkar, S. (International Journal of Economic Plants, 2019)
The experiment was performed from September, 2014 to April, 2015 in order to determine the intensity of infestation by fruit flies in guava orchard in the northern district of West Bengal, India. A survey was conducted in the major guava growing areas of the terai and hilly region of West Bengal especially in northern district. From each location altogether one hundred (100) fruits were collected randomly at three times from the orchard and then taken to the laboratory and examined critically for fruit fly infestation. During 2014, results revealed that highest fruit fly infestation (25.00%) was reported from Posarir Hat and lowest (9.67%) from Kharibari. However, in the next year, i.e. during 2015, maximum fruit fly infestation (28.33%) was reported again from Posarir Hat and lowest (8.67%) from Matigara.